Long‐term acoustic monitoring of nonstereotyped blue whale calls in the southern Indian Ocean. Issue 2 (31st January 2023) - Torterotot, Maëlle; Samaran, Flore; Royer, Jean‐Yves
Abstract: Monitoring the presence of blue whale ( Balaenoptera musculus ssp.) stereotyped calls has been a widely used method to assess the different populations' distribution worldwide. All blue whale populations also produce nonstereotyped vocalizations, or D‐calls. Here, we monitored the presence of D‐calls in long‐term records from a large hydrophone array located in the open southern Indian Ocean, using an automated detection method and manual validation of the detections. D‐calls were detected at all sites of the array, which extends from 24°S to 56°S, but the majority of them were detected at the two southernmost sites. We observed a latitudinal shift in their seasonal occurrence, with more D‐calls in the north during austral autumn and winter and more in the south during austral spring. The geographical occurrence of D‐calls compared to that of songs indicates that blue whale acoustic behavior switches from a song‐intensive and sparse‐D‐call emission in the north to song‐moderate and more intensive D‐call emissions in the south. These findings support the hypothesis that both call types are used for different purposes, as D‐calls are mainly detected around foraging grounds and songs in wintering grounds. Monitoring both call types might therefore be a relevant acoustic indicator of blue whale behavior.